Functional fantasies: the regulatory role of grandiose fantasizing in pathological narcissism - Finch, Ellen F.; Hooley, Jill M. (Frontiers in Psychiatry, 2023)
Pathological narcissism is characterized by maladaptive efforts to maintain a bolstered but fragile sense of self. Clinical theory suggests that grandiose fantasizingengaging in fantasies of success, power, brilliance, or beautymay be one way that people higher in narcissism self-regulate. However, no empirical research has directly assessed this hypothesized regulatory function. Using a novel experimental paradigm, we demonstrate that people scoring higher in narcissism are more likely to choose to engage in grandiose fantasizing to make themselves feel better than are people scoring lower in narcissism. Further, we show that grandiose fantasizing is more effective at improving affect among participants scoring higher in narcissism than those scoring lower in narcissism, whereas more generally positive future thinking was equally effective at improving affect across levels of narcissism. This work provides empirical support for an oft-cited clinical theory that grandiose fantasizing is regulatory. The findings increase confidence that grandiose fantasizing is not just a general tendency among people higher in narcissism, but rather serves a functional (and potentially adaptive) role.